Signs of Bruxism and Temporomandibular Disorders among Patients with Bipolar Disorder - Gurbuz Ozlem; Altinbas Kursat; Oflezer Ceyhan; Kurt Erhan; Arslan Mehtap Delice (Balkan Stomatological Society, 2017)
Background/Aim: There is an abundance of data regarding temporomandibular disorders (TMD) and bruxism specific to patients with bipolar disorder (BD). This study aimed to investigate the prevalence of TMD signs in subjects with and without BD. Material and Methods: The case group included 242 adult patients (103 men and 139 women) with BD and and the control group included 187 subjects without BD (89 men and 98 women). The case and control groups were compared for the presence of bruxism and the signs of TMD including muscle and temporomandibular joint (TMJ) tenderness to palpation, limitation of maximum mouth opening, and TMJ sounds. Results: The frequency of at least one sign of TMD was significantly higher in patients with BD (191 ⁄242, 78.9%) than the control group (95 ⁄187, 50.8%) (p<0.001). Statistically significant differences were found between the case and control groups in terms of joint pain on palpation (p<0.05), masseter muscle pain on palpation (p<0.01), joint clicks (p<0.001) and limited mouth opening (p<0.001). Bruxism was significantly higher in patients with BD (49.6%) than the control group (19.8%) (p<0.001). Conclusions: Patients with BD appear to be more prone to having TMD signs and bruxism compared to the control group, but this comorbidity should be better understood by further studies.